Experimental Studies on Magnetorheological Fluids - GENÇ, SEVAL (Elsevier, 2022)
Smart materials are defined as the materials having properties that can be tuned or altered under externally applied fields. These materials are usually polycrystalline or single crystal in their solid state. These smart materials exhibit properties such as ferroelectricity, pyroelectricity, piezoelectricity, and magnetostriction. Another class of smart materials is known as the “field responsive fluids”. Magnetorheological (MR) fluids, electrorheological (ER) fluids, ferrofluids, and some gels belong to this group. A common property of these fluids is that they are all dispersions of particles in a carrier liquid and their properties are controlled by externally applied magnetic or electrical field. MR fluid can be defined as ferromagnetic or ferrimagnetic particles dispersed in an organic or aqueous carrier liquid. MR fluid has reversible and tunable ability to transform from liquid to viscoelastic solid in fractions of a millisecond when subjected to a magnetic field. MR fluid has a consistency like paints in the “off-state” (B ¼ 0T) regime. In the “on-state” (B a 0T) regime the magnetic particles line up, forming chain-like structure in the direction of the applied magnetic field in order to minimize the magnetic dipole interactions between the particles. This chain alignment causes a considerable increase in the yield stress. This increase is non-linear since the particles are ferro or ferrimagnetic. Depending on the composition, particle size, volume fraction, magnetic saturation, and flux density, the yield stress can go up to 100 kPa (Genç and Phulé, 2002). The ferromagnetic or ferrimagnetic magnetic phase is multi-domain with low coercivity and high saturation magnetization. The diameters of the particles range from 0.01 to 20 mm. Due to its high saturation magnetization (Ms ¼ 203.7 emu/gr), carbonyl iron (CI) produced by decomposition iron penta-carbonyl (Fe(CO)5), is the most commonly used magnetic material (Cullity and Graham, 2010). Besides iron, cobalt, nickel, iron oxides (Fe3O4, Fe2O3), ferrites, and transition metal alloys are also used in the synthesis of the MR fluid. Silicone oils, synthetic or semi-synthetic oils, lubricating oils and mineral oils, many other polar organic liquid and water have all been reported to be used as carrier liquid (Genc and Derin, 2012). Due to their field dependent rheology, MR fluid is used in automobile dampers, (Abu-Ein et al., 2010; Zeinali et al., 2016; Attia et al., 2017), clutches (Hema Latha et al., 2017), and brakes (Kumbhar et al., 2015). They are also utilized in polishing devices (Jha and Jain, 2009), loud speakers, vacuum sealing, cancer therapy (Liu et al., 2001). Although iron having high saturation magnetization could be a good candidate for magnetic phase, its high density could be a disadvantage. Mismatch between the density of the magnetic particles and carrier liquid causes sedimentation which deteriorates the MR effect. To improve the sedimentation stability without sacrificing the MR effect is a challenge. One way to make a stable suspension is to coat the magnetic particles with a surfactant in order to create steric stabilization (Phulé et al., 1999). The stability could also be improved by using nanoparticles such as magnetite (Fe3O4), because thermodynamic forces can overcome the gravitation settling when the particle size decreases to a critical value (Rosensweig, 2014). Microcrystalline cellulose, carbon nanotubes, silica, and graphene oxide, nano-hollow Fe3O4 spheres are other additives that are investigated by various scientists (Ashtiani et al., 2015). After the brief introduction of MR fluids, in the rest of the paper, the recent experimental studies of the MR fluids will be discussed. These studies will include the improvement of MR effect and sedimentation stability, as well as the experimental findings of the rheological and stability measurements.